Pengaruh profitabilitas, operating leverage, sales growth, struktur aset, CEO female dan CEO tenure terhadap struktur modal - Febtiani, Eka Tiara; Isbanah, Yuyun (Jurnal Ilmu Manajemen, 2024)
Capital structure is a combination of debt and equity in the company's long-term financial structure. This research aims to determine the effect of profitability, operating leverage, sales growth, asset structure, CEO female and CEO tenure on capital structure in the infrastructure sector listed on the Indonesia Stock Exchange for the period 2018-2022. The type of data used is quantitative data sourced from secondary data. The population of this research is infrastructure sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique used purposive sampling and 14 companies were obtained as samples in this research. This research uses panel data regression analysis techniques which are analyzed using STATA 17. The results show that asset structure has a significant negative effect on capital structure, while profitability, operating leverage, sales growth, CEO female and CEO tenure do not have a significant effect on structure capital. Infrastructure sector companies should always pay attention to the company's asset structure because improving the asset structure contributes to optimizing the company's capital structure. This is because a company with a high asset structure value means it has a large amount of its own capital, thereby reducing the company's dependence on debt in order to achieve an optimal company capital structure. Companies must also be able to balance debt and equity and make the best use of their fixed assets in order to get large returns and minimize the risk of debt.